Augmented reality (AR) tasrif in teaching and learning Arabic morphology - Md. Noor, Mohamad Lukman Al Hakim; Ab Hamid, Ahmad Rauyani; Hashim, Muhammad Faizuddin; Ab Hassan, Nurliyana; Md Ghalib, Mohd. Feham (2020)
Augmented Reality (AR) can help students interact with the real world and enhance their learning experiences. However, research is lacking to its use in learning Arabic Morphology (AM) especially for teaching Arabic subjects. This study employed the ADDIE model of instructional design to develop a course for teaching and learning AM. For the first stage of ADDIE, a needs analysis was conducted on 61 Arabic major students from the Centre for Foundation Studies, International Islamic University Malaysia to find out which topics of AM that the students had difficulty the most and what would be their preferences in learning AM via AR. The analysis revealed that Arabic Pattern Verbs scored the most difficult in AM. Based on their needs and preferences, a mobile application, AR Tasrif, was designed.